Hepatitis C Virus Infection Preceding an Outbreak of Human Immunodeficiency Virus Among Persons Who Inject Drugs—Kanawha County, West Virginia, 2019–2021. (29th July 2022) - Hudson, Alana G; Bonacci, Robert A; Moorman, Anne C; Penley, McKenna; Wilson, Suzanne M; Hoffman, Jessica L; Thomasson, Erica R; McClung, R Paul; Bixler, Danae
Abstract: Of 65 cases during a human immunodeficiency virus (HIV) outbreak among persons who inject drugs (PWID) in West Virginia (2019–2021), 61 (94%) had hepatitis C diagnosed a median of 46 months prior to HIV diagnosis. Hepatitis C diagnosis among PWID should trigger improved access to prevention and treatment services.